2001
DOI: 10.1016/s0002-9440(10)63993-4
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Amyloid-Bri Deposition and Its Association with Neurofibrillary Degeneration in Familial British Dementia

Abstract: Familial British dementia (FBD), pathologically characterized by cerebral amyloid angiopathy (CAA), amyloid plaques, and neurofibrillary degeneration, is associated with a stop codon mutation in the BRI gene resulting in the production of an amyloidogenic fragment, amyloid-Bri (ABri). The aim of this study was to assess the distribution of ABri fibrillar and nonfibrillar lesions and their relationship to neurofibrillary pathology, astroglial and microglial response using immunohistochemistry, confocal microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
111
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 44 publications
8
111
1
Order By: Relevance
“…The increase of total Tau leads to higher levels of its protein levels, a condition that favors phosphorylation and aggregation, as demonstrated with mutant Tau, when unable to bind tubulin (Holton et al ., 2001; Bunker et al ., 2006). We observed that Aβ monomers, in parallel with an increase of Tau protein levels, impair proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of total Tau leads to higher levels of its protein levels, a condition that favors phosphorylation and aggregation, as demonstrated with mutant Tau, when unable to bind tubulin (Holton et al ., 2001; Bunker et al ., 2006). We observed that Aβ monomers, in parallel with an increase of Tau protein levels, impair proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The third hypothesis is supported by the occurrence of Tau pathology in different types of cerebral amyloidosis (Holton et al ., 2001; Giaccone et al ., 2008). …”
Section: Introductionmentioning
confidence: 99%
“…This early onset disorder, clinically characterized by progressive dementia, cerebellar ataxia, and spastic paraparesis, was first described by Worster-Drought et al (1933) as a familial presenile dementia with spastic paralysis (10 -13). The neuropathology of FBD is remarkably similar to that of FDD and AD, particularly in regard to the presence of neurofibrillary tangles ultrastructurally composed of classical paired helical filaments (14,15). As in FDD, the stop to Arg point mutation in FBD also eliminates the BRI2 stop codon and generates a longer than normal precursor ABriPP.…”
mentioning
confidence: 86%
“…The genetic defect underlying FBD was recently identified (2); affected patients have a T to A transversion (TGA3 AGA) at the stop codon of the BRI 2 gene (3-5) that results in the generation of an arginine codon and a longer open reading frame that encodes a 277-amino acid protein, termed BRI-L (2). A 34-amino acid peptide, termed ABri, generated by endoproteolytic processing of this mutant precursor protein is deposited in the brains of FBD patients (2,6). Interestingly, a different genetic defect of the BRI 2 gene was found in another rare, autosomal dominant, neurodegenerative disease, familial Danish dementia (FDD) (7).…”
mentioning
confidence: 99%